In vitro and in vivo characterization of oridonin analogs as anti-inflammatory agents that regulate the NF-κB and NLRP3 inflammasome axis - Ou, Huiping; Wu, Zhanpan; Ning, Jinhua; Huang, Qiufeng; Wang, Wancun; Yang, Guochun; Zhou, Yingxun; Hou, Anguo; Li, Peng; Chen, Lingyun; Jin, Wen Bin (Frontiers in Pharmacology, 2025)
IntroductionA series of oridonin hybrids were synthesized and evaluated for anti-inflammatory potential, focusing on their ability to inhibit NO production in RAW264.7 cells and their therapeutic prospects for NLRP3-driven disorders.MethodsAnti-inflammatory activity was assessed by measuring NO inhibition in LPS-stimulated RAW264.7 cells. The most active compound, 4c, was further analyzed using ELISA and WB to evaluate its effects on inflammatory proteins (p-NF-κB, p-IκB, NLRP3, IL-6, IL-1β, COX-2, iNOS). In vivo efficacy was tested in a murine acute lung injury model, with RT‒qPCR and WB used to assess inflammatory markers in lung tissues. Molecular docking predicted 4c’s binding mode with NLRP3, while RNA-seq and RT‒qPCR identified differentially expressed genes.ResultsCompound 4c significantly inhibited NO production and suppressed key inflammatory proteins in vitro. In vivo, it alleviated acute lung injury, reduced IL-6 and TNF-α mRNA levels, and inhibited NLRP3, p-NF-κB, and IL-6 protein expression. Docking suggested covalent binding to NLRP3. RNA-seq revealed 4c upregulated Trdc, Stfa2, and Gsta2 while downregulating Spib, Csf2, and Nr4a1.DiscussionCompound 4c demonstrates potent anti-inflammatory effects via NLRP3 pathway inhibition and modulation of inflammatory genes. These findings highlight oridonin hybrids, particularly 4c, as promising candidates for NLRP3-driven inflammatory disorders, warranting further investigation.